1999
DOI: 10.1136/bjo.83.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood flow characteristics in central retinal vein occlusion and effects of panretinal photocoagulation treatment: an investigation by colour Doppler imaging

Abstract: Conclusion-This study suggests that impaired arterial blood flow observed in patients with CRVO may be partly related to secondary changes in the retrobulbar arterial circulation as a result of enhanced arterial resistance following CRVO. These data also demonstrate that PRP treatment decreases retinal and ophthalmic blood flow velocities in patients with ischaemic CRVO. (Br J Ophthalmol 1999;83:50-53)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…By using CDI in the non-ischemic CRVO cases, Avunduk et al [15] reported that OA and CRA blood flow velocities and RI did not differ significantly from their fellow eyes. Significantly lower blood flow velocities and higher RI were found in the CRA and OA of the patients with non-ischemic CRVO compared with healthy controls [16].…”
Section: Discussionmentioning
confidence: 99%
“…By using CDI in the non-ischemic CRVO cases, Avunduk et al [15] reported that OA and CRA blood flow velocities and RI did not differ significantly from their fellow eyes. Significantly lower blood flow velocities and higher RI were found in the CRA and OA of the patients with non-ischemic CRVO compared with healthy controls [16].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in arterial and/or venous flow during the course of ischaemic CRVO are well known, but retinal blood flow changes after panretinal photocoagulation treatment are still controversial. Avunduk et al. (1999) reported that with colour Doppler imaging, reduced blood flow velocity in eyes with CRVO with laser treatment decreased even further compared to the contralateral eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Avunduk et al 23 also investigated the blood flow velocities of the fellow eyes of CRVO patients and reported that those of the ophthalmic and central retinal arteries of the fellow eyes of CRVO patients were decreased compared with those of normal controls. They suggested that some hemodynamic abnormalities in the retrobulbar arterial circulation might be present before the clinical onset of CRVO.…”
Section: Erg In the Fellow Eyementioning
confidence: 95%
“…The authors suggested that reduced rod phototransduction may be secondary to reduced choroidal perfusion. In another study, Avunduk et al 23 reported the blood flow velocities of the ophthalmic and central retinal arteries measured by using color Doppler imaging in cases with CRVO and normal controls. In cases with CRVO, a primary bloodstream decrease in the retrobulbar arterial circulation had already been caused by arteriosclerosis and atherosclerosis, and a secondary bloodstream decrease was caused by developing CRVO with increased vascular resistance through the capillary bed to the arterial side.…”
Section: Erg In the Affected Eye (First Recordings)mentioning
confidence: 97%